CONSUMER BEHAVIOUR TOWARDS ONLINE SHOPING - SHARMA, POONAM (INTERNATIONAL JOURNAL OF RESEARCH PEDAGOGY AND TECHNOLOGY IN EDUCATION AND MOVEMENT SCIENCES, 2023)
Online marketing has gained huge popularity and importance all over the world. Considering the wide range of benefits, it provides to marketers as well as customer. The growing number of Internet user in India provides a bright prospect for online shopping. If E-marketers know the key factors affecting behavior of customers and its relationship then they can formulate their marketing strategies to convert potential customers into loyal ones and retaining existing online customers. This research paper highlights on the consumer behaviors of people residing in the Jammu  City, their behavior towards online shopping through e commerce websites such as Amazon, Flip kart etc.